Pengaruh Pasokan Bahan Baku dan Tuntutan Pelanggan Bisnis pada Strategi Produk-Pasar dan Bauran Pemasaran serta Dampaknya pada Penjualan Studi terhadap Industri Spinning di Jawa Barat - Sumachdar, Endang (Business and Management Review, 2010)
Global competition is increasing, that situation force many economic players to be superior to win the market. Hence, every single firm within national industry should have a competitive advantage to be survived in this chaotic global competition. One of the world large industry is a spinning industry and recently the Indonesian spinning industry performance has been declining. This phenomenon exists because the national spinning industry doesn’t have a competitive advantage to succeed and survive in the tight global competition. To anticipate the decline and to promote the industry sustainability, the spinning industry should reengineer its marketing strategy, especially to be more responsive in creating and utilizing opportunity, as well as, in anticipating threats in the marketing environment. The spinning industry strategy on market segmenting, targeting, positioning, and marketing mix should consider the raw material supplier as well as its business customer. Hence, the industry could synergize all factors to improve the industry/firm performance that can be resulted on the increase of sales volume. This research focus on how spinning industry/firm can create its competitive advantage from the perspective of marketing management, especially on examining the influence of raw material supplies and the business customer requirement to segmenting, targeting, positioning, and marketing mix strategy with its implication on the sales volume. The observation unit is spinning industry/firms which are stated as the member of Indonesian Textile Association in Java Region. The research result shows that the number of spinning firms is greater than the number of raw material supplier. This situation creates the scarcity of raw material, so the supplier has stronger bargaining position power than the spinning firm. Consequently, the supplier has more ability to control the provision of  raw material, such as: the number of fiber, the quality, the price, and the sustainability of delivery. The provision of raw material supplies and customer requirements are the two factors that have a strong and significant influence to product-market strategy and marketing mix. Those two factors also have a strong and significant influence to the sales volume. Between the two factors, the supplies have the most significant influence to the sales volume. The major indicators that contribute the most significant influence to the sales volume are the price and quality as the indicators of supplies; and the accesibility to understand customer wants and demands as the indicator of the customer requirement. In determining market segmentation, the spinning firms are not only have to consider the profitability proxy but also the accesibility in executing the marketing program. The segmentation should be determined based on the firms capability and availability of resources. Thus, the firms could provide their customer requirements. Increasing product differentiation and variation that are required by the customers has also be fitted to the competitor strategy and consumer characteristics. Keywords: spinning, raw material supply, business customer requirements, product- market strategy, marketing mix and sales